2015
DOI: 10.1093/rheumatology/kev012
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis and the prevalence of diabetic retinopathy

Abstract: Findings support the 1964 paradox observing decreased diabetic retinopathy in patients with RA. These findings pose new questions regarding whether RA physiology or treatments protect against diabetic retinopathy and how intraocular factors vary in contrast to adverse vascular changes elsewhere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Using iNOS knockout mice, investigators were able to demonstrate a direct role between iNOS and the development of DR in its early stages [118]. Moreover, it has been reported that patients treated for rheumatoid arthritis with salicylate-based drugs had lower incidences of DR [119, 120], indicating a possible role for anti-inflammatory drugs in modulating DR progression. In addition to hyperglycemic conditions, the alteration in retinal fatty acid metabolism, possibly via AGE/RAGE interactions and the activation of the MAPK pathway, can lead to chronic inflammation due to a decrease in retinal n-3 polyunsaturated fatty acids (PUFAs), such as docosohexanoic acid (DHA) [121].…”
Section: Molecular Mechanisms Of Diabetic Retinopathymentioning
confidence: 99%
“…Using iNOS knockout mice, investigators were able to demonstrate a direct role between iNOS and the development of DR in its early stages [118]. Moreover, it has been reported that patients treated for rheumatoid arthritis with salicylate-based drugs had lower incidences of DR [119, 120], indicating a possible role for anti-inflammatory drugs in modulating DR progression. In addition to hyperglycemic conditions, the alteration in retinal fatty acid metabolism, possibly via AGE/RAGE interactions and the activation of the MAPK pathway, can lead to chronic inflammation due to a decrease in retinal n-3 polyunsaturated fatty acids (PUFAs), such as docosohexanoic acid (DHA) [121].…”
Section: Molecular Mechanisms Of Diabetic Retinopathymentioning
confidence: 99%
“…Nonetheless, studies suggest a possible connection between arthritis and diabetes, specifically that individuals with rheumatoid arthritis, an inflammatory form of arthritis, may have a higher likelihood of developing type 2 diabetes. [32,33] Hyperglycemia, hypertension, dyslipidemia, and kidney disease are the most common risk factors for diabetic retinopathy, frequently present in type 2 diabetes patients. Therefore, those with both arthritis and type 2 diabetes may have a heightened risk of developing diabetic retinopathy due to these shared factors.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the speculated involvement of immune responses to type II collagen in the pathogenesis of both DR and RA, it seems rather uncommon that these two diseases develop simultaneously. In fact, it was previously reported that patients with RA were less predisposed to develop DR [ 67 ]. A number of studies have indicated the frequency of HLA-DR and -DQ antigens that were associated with disease susceptibility were different between DR and RA patients [ 15 , 16 , 68 ].…”
Section: Immunological Divergence Between Diabetic Retinopathy and Rheumatoid Arthritismentioning
confidence: 99%